Optimasi Kinerja Pegawai Kecamatan Samarinda Utara: Peran Standar Operasional, Penempatan, dan Profesionalisme - Rini, Anggraita Fuspa; Sabtohadi, Joko; Hadiyanti, Sofia Ulfa Eka; Rahmadi, Muhammad Harry (Equator Journal of Management and Entrepreneurship (EJME), 2024)
The purpose of this research is to see the influence of the variables of standard operating procedures, placement and professionalism on employee performance, which variable has the most influence on employee performance in North Samarinda District in Samarinda City. The research method used in this research is a quantitative approach. The data collection method used is a questionnaire given to 41 respondents as a sample offline. Validity and reliability tests are measuring instruments used to obtain valid and reliable results in data collection and calculation. Normality test, classical assumption test and hypothesis testing will be used to process the collected data. The analysis results show that partially the standard operating procedure variable has no significant effect on employee performance, the placement variable has a significant effect on employee performance and the professionalism variable has no significant effect on employee performance. While simultaneously the variables of standard operating procedures, placement and professionalism have a significant effect on the performance of employees of the North Samarinda District in Samarinda City.